Letter's recognition in early literacy through snakes and ladder games - Khairul Amri; Rizkia Mauliza; Syarfina Syarfina (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
This study aims to determine the process of applying the game of snakes and ladders in increasing letter recognition in children aged 4-5 years at the Pembina State Kindergarten of Langsa City and to see the activities of children in learning to recognize letters using the game of snakes and ladders. This research is a type of Classroom Action Research (CAR). The subjects in this study were the 17 children of group B of the Pembina State Kindergarten in Langsa City. The method used in data collection, namely, observation and interviews. Data collection techniques using descriptive quantitative. The results of the study showed that the game of snakes and ladders can improve children's ability to recognize letters. At the time of pre-action observation, the percentage of ability to recognize letters was 43% with indicators recognizing letter symbols 15%, making meaningful scribbles 15%, writing and speaking letters (A-Z) 11.7%. In the first cycle the percentage of increase in children's letter recognition was 66.4% with a category of 15 children starting to develop 2 children developing according to expectations (BSH) with indicators recognizing letter symbols 20.5%, making meaningful scribbles 23.5%, writing and writing. pronounce the letters (AZ) 22%. Furthermore, in cycle II there was a very significant increase, namely 98% with the criteria of 13 children developing as expected (BSH) and 4 children developing very well (BSB) with indicators recognizing letter symbols 33%, making meaningful scribbles 32%, writing and speaking letters (AZ) 32%. Based on the description of the results of the research before the action, cycle I and cycle II, it can be concluded that the snake and ladder game is able to improve the ability to recognize children's letters in the Pembina State Kindergarten of Langsa City.